Canva Magic: Menggali Perilaku Pengguna dalam Membangun Brand Identity UMKM Bandung di Era Digital - Panji Pramuditha; Harto, Budi; Neng Siti Lutfia Alfani Kurnia Sari (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
This research focuses on the challenges faced by Micro, Small and Medium Enterprises (MSMEs) in Bandung in creating a strong identity in the digital era. There are many MSMEs that struggle to create attractive and effective promotional content, so they need tools that can help them in the design process. The purpose of this study is to find out how MSMEs can use the Canva application to improve their design skills and strengthen their identity. The method used in this research is a quantitative approach by distributing questionnaires to 100 MSME employees who use Canva. The data was analyzed to determine the frequency of application use, the most frequently used features, and the impact of Canva on user identity development. The findings showed that after attending Canva training, MSMEs experienced a significant improvement in terms of the ability to create visually appealing content. In addition, Canva is quite effective in increasing the visibility and position of MSMEs on digital platforms.